Sociolinguistic and didactic considerations on English-Spanish cross-cultural awareness - Ardila, J. A. G.; Neville, Jane (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Foreign language teaching has become one of the main beneficiaries of many linguistic theories stemmed from the realms of anthropology and ethnolinguistics. However, albeit such theories are now believed irrefutable, they are, nonetheless, neglected in many university syllabi. Certainly, not only should socio-cultural awareness be instructed in advanced language courses, furthermore paralinguistic features are indeed necessary in order to teach how to communicate effectively in a foreign language. This article draws from sociology in order to denounce the astounding paralinguistic disparities between the English and the Spanish languages, and to urge university syllabus-makers (especially of Spanish/English for business) to account for them.